Functional connectivity of the reading network is associated with prenatal polybrominated diphenyl ether concentrations in a community sample of 5 year-old children: A preliminary study. (January 2020) - Margolis, Amy E.; Banker, Sarah; Pagliaccio, David; De Water, Erik; Curtin, Paul; Bonilla, Anny; Herbstman, Julie B.; Whyatt, Robin; Bansal, Ravi; Sjödin, Andreas; Milham, Michael P.; Peterson, Bradley S.; et al.
Highlights: Polybrominated Diphenyl Ethers (PBDE), used as flame retardants, cross the placenta. PBDE exposure predicts reduced efficiency of the brain's reading network. Efficiency of the brain's reading network predicts word reading in 5 year-olds. Prior findings show PBDE exposure predicts reading problems in 8 year-old children. PBDE may represent an overlooked factor in the etiology of reading problems. Abstract: Genetic factors explain 60 percent of variance in reading disorder. Exposure to neurotoxicants, including polybrominated diphenyl ethers (PBDEs), may be overlooked risk factors for reading problems. We used resting-state functional magnetic resonance imaging (rs-fMRI) to examine associations between prenatal PBDE concentrations and functional connectivity of a reading-related network (RN) in a community sample of 5-year-old children (N = 33). Maternal serum PBDE concentrations (∑PBDE) were measured at 12.2 ± 2.8 weeks gestation (mean ± SD). The RN was defined by 12 regions identified in prior task-based fMRI meta-analyses; global efficiency (GE) was used to measure network integration. Linear regression evaluated associations between ∑PBDE, word reading, and GE of the RN and the default mode network (DMN); the latter to establish specificity of findings. Weighted quantile sum regression analyses evaluated the contributions of specific PBDE congeners to observed associations. Greater RN efficiency was associated with better word reading in these novice readers. Children with higher ∑PBDE showed reduced GE of the RN; ∑PBDE was not associated with DMN efficiency, demonstrating specificity of our results. Consistent with prior findings, ∑PBDE was not associated word reading at 5-years-old. Altered efficiency and integration of the RN may underlie associations between ∑PBDE concentrations and reading problems observed previously in older children.